2022
DOI: 10.1038/s41586-022-04826-7
|View full text |Cite
|
Sign up to set email alerts
|

A first update on mapping the human genetic architecture of COVID-19

Abstract: Data availabilitySummary statistics generated by COVID-19 Host Genetics Initiative are available online (https://www.covid19hg.org/results/r6/). The analyses described here use the freeze 6 data. The COVID-19 Host Genetics Initiative continues to regularly release new data freezes. Summary statistics for samples from individuals of non-European ancestry are not currently available owing to the small individual sample sizes of these groups, but the results for 23 loci lead variants are reported in Supplementary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 14 publications
3
80
2
Order By: Relevance
“…The resulting score (either 0, 1, or 2) for each mask was then regressed on each of our three phenotypes using logistic regression, controlling for age, age^2, sex, sex*age, sex*age 2 , and 10 common variant (MAF > 1%) genetic principal components (the same covariates as for COVID-19 HGI GWASs [ 7 , 8 ]). Additionally, given that population genetic structure and its confounding effect on phenotypes is different at the rare variant level [ 26 ], we also used the first 20 genetic principal components from rare variants (MAF<1%) as covariates in all our analyses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting score (either 0, 1, or 2) for each mask was then regressed on each of our three phenotypes using logistic regression, controlling for age, age^2, sex, sex*age, sex*age 2 , and 10 common variant (MAF > 1%) genetic principal components (the same covariates as for COVID-19 HGI GWASs [ 7 , 8 ]). Additionally, given that population genetic structure and its confounding effect on phenotypes is different at the rare variant level [ 26 ], we also used the first 20 genetic principal components from rare variants (MAF<1%) as covariates in all our analyses.…”
Section: Resultsmentioning
confidence: 99%
“…However, given that COVID-19 critical illness remains a rare phenomenon [ 51 ], our severe disease phenotype results are unlikely to be strongly affected by this. Finally, the use of population control is a long-established strategy in GWAS burden tests [ 7 , 8 , 11 , 22 , 52 ], and the statistical power gain from increasing our sample size is likely to have counter-balanced the misclassification bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, MUC22 is approximately 100 kb from CCHCR1 gene, the most important signal in the MHC region for Covid-19 susceptibility, according to the Covid-19 Host Genetics Consortium (Covid19hg - ). All CCHCR1 variants associated with Covid-19 ( 29 , 61 ) are intronic and were not captured by our genotyping method (whole-exome sequencing). The exomic CCHCR1 variants included in our survey do not correlate with Covid-19 severity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the most recent GWAS study on European, Latino, and African American patients revealed novel risk variants associated with COVID-19 severity, which were located in chromosomes 19p13.3, 12q24.13, and 21q22.1 [ 6 ]. Most recently, an updated GWAS study by COVID-19 Host Genetics Initiative additionally revealed 11 significant loci, which consisted of three genes in new loci ( SFTPD , MUC5B, and ACE2 ), compared with 13 loci previously described [ 8 ]. Scientific reports in Asian populations also discovered host genetic factors related to COVID-19 infection and progression such as ACE2 in Chinese patients [ 9 ], ACE2 and TMPRSS2 in Japanese patients [ 10 ], 5q32 and 12q22 in Thai patients [ 11 ], and HLA system in South Asian patients [ 12 ].…”
Section: Introductionmentioning
confidence: 99%